Cluster Differentiation 133 Expression in Patients With Basal Cell Carcinoma: an Immunohistochemical Review - Rahmat Firdaus Dwi Utama; Nugrohoaji Dharmawan; Ammarilis Murastami; Nurrachmat Mulianto; Novan Adi Setyawan (International Journal Labs, 2025)
Basal cell carcinoma (BCC) is the most common non-melanoma skin cancer in humans, developing on skin exposed to ultraviolet light and rarely metastasizing. Cancer stem cell markers such as CD133 have been extensively studied in various malignancies, but their expression in BCC remains controversial and has not been widely studied in Indonesia. Determine the difference in CD133 expression between BCC patients and normal skin. Analytical observational study with a case control design was conducted at Dr. Moewardi General Hospital in Surakarta from April to July 2025. The sample included 13 BCC tissues and 13 normal skin controls taken by consecutive sampling from paraffin blocks from 2021-2024. CD133 immunohistochemical staining was performed with Allred scoring by a single pathologist on at least four random fields of view. Descriptive analysis presented demographic characteristics and Allred scores, while the Chi square test was used to compare CD133 expression between groups with significance at p < 0.05. The mean CD133 Allred score was 7.15 ± 0.56 in KSB tissue and 7.31 ± 0.48 in normal skin. Strongly positive CD133 expression was found in 12/13 BCC patients and 13/13 normal skin. Chi square analysis showed no significant difference in CD133 expression between the BCC and normal skin groups (p=0.308). CD133 expression based on the Allred score did not differ significantly between BCC tissue and normal skin, indicating that CD133 is not useful as a single marker for the diagnosis or prognosis of KSB